Design and characterization of a melt electrostatic precipitator for advanced drug formulations - Justen, Anna; Weltersbach, Alina Faye; Schaldach, Gerhard; Thommes, Markus (Technische Universität Dortmund, 2024)
Electrostatic precipitators (ESP) are especially known for the efficient separation of micron and submicron particles from aerosols. Wet electrostatic precipitators are particularly suitable for highly resistive materials. Using these, particles can be directly transferred into a liquid for further processing or safer handling, which is advantageous for either hazardous or valuable materials. In this work, a wet ESP, which enables the separation of highly resistive particles into a heated liquid, was designed and investigated. To do this, spray-dried drug particles were embedded in a molten sugar alcohol to enhance the drug dissolution rate. After cooling, the solidified product showed advantageous properties such as a high drug dissolution rate and easy handling for further processing. For the design of the wet ESP, different discharge electrode configurations were tested. A wall film served as the collection electrode, which was generated by a specially designed distributer die. A laminar flow regime was achieved with a homogeneous film serving as the collection electrode, which is particularly important for a high separation efficiency. A prototype was designed and constructed in this respect. The particle separation into hot liquids or onto hot surfaces is challenging due to thermal effects in ESPs. The influence of thermophoresis and drag force on the particle transport was investigated, and optimum operation parameters were found for the present ESP. A broad field of applications can be covered with the presented device, where particles are embedded in even hot liquids to form liquid suspensions or, as it is presented here, solid dispersions. The dissolution of the drug-containing solid dispersion was studied in vitro. A remarkably faster drug dissolution was observed from the solid dispersion, as compared to a powder mixture of the drug and xylitol.
Processes;12(1)
Keywords: Electrostatic precipitation; Wall film; Thermophoresis; Solid dispersion; Drug dissolution; 660; Elektroentstaubung; Thermodiffusion; Feststoff; Dispersion; Arzneimittel; Formulierung <Technische Chemie>